The role of management control systems in planned organizational change: An analysis of two organizations - Chenhall, Robert H.; Euske, K.J. (Accounting, Organizations and Society, 2007)
In the management control literature there is growing interest in the role of management control systems (MCS) in planned organizational change. The existing literature is concerned with either rational, technical change principles or more social and political interpretations of MCS facilitated change. This paper aims to extend this literature by combining technical approaches to MCS facilitated change with a behavioral approach in the study of two similar organizations. Moreover, the paper employs a holistic approach to change to develop a comprehensive understanding of the role of MCS in planned organizational change. A framework by Huy [Huy, Q. N. (2001). Time, temporal capacity, and planned change. Academy of Management Review 26(4), 601–623] is used to provide an integrative approach that focuses on both rational, systematic practices and the behavioral processes involved in their implementation. This is achieved by identifying four idealized intervention types: commanding, engineering, teaching and socializing. Understanding the application of these four intervention types requires analysis of the way they interact through time.